Penggunaan Zeolit sebagai Pendegradasi Senyawa Permetrin dengan Metoda Fotolisis - Zilfa, Zilfa; Suyani, Hamzar; Safni, Safni; Jamarun, Novesar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The research about the degradation of permethryn compound has been done by photolysis method using natural zeolyte as catalyst.Permethryn is one syntetic pyretroid pesticides that low toxicity for mammals but it is high toxicity for fishs, insects and water microorganisms.Zeolyte is aluminosilicate minerals that can be used for degradation of permethryn. Percentage degradation of permethryn is lower withoutzeolyte than using zeolyte as catalyst by photolysis method. 20 mg/l permethryn solution could be degraded 5.40% after 120 minutesirradiation, while by adding 0.20 g natural zeolyte, permethryn could be degraded 69.70